What is the inverse equation of y=4x-3?

1 Answer
Mar 18, 2018

f^{-1}:y=(x+3)/4

Explanation:

When finding the inverse of a function it helps to think of the function in terms of x and y.

f:y=4x-3

where f is a function stating that y is equal to the right hand side.

Then you switch the x's and y's and write it as the inverse function for x.
f^{-1}:x=4y-3

However, to get the inverse function for y, we must rearrange the equation to get y on the left hand side along with f^{-1}: so that we get the expression f^{-1}:y=some value.

f^{-1}:x=4y-3

f^{-1}:x+3=4y //add 3 to both sides

f^{-1}:(x+3)/4=y //divide both sides by 4

Therefore, the inverse function is f^{-1}:y=(x+3)/4